2009
DOI: 10.5507/bp.2009.012
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of Cardiovascular Risk Factors and Cosmetic Side Effects in Kidney Transplant Recipients After Conversion to Tacrolimus

Abstract: Aims:Tacrolimus and Cyclosporine A (CyA) are cornerstones in immunosuppressive therapy. Cyclosporine side eff ects include hypertension and hypercholesterolemia both of which may increase the risk of cardiovascular mortality, gingival hyperplasia and hirsutism are known to reduce quality of life. The aim of this prospective study was to evaluate changes in cardiovascular risk profi le and cosmetic side eff ects after conversion from CyA to tacrolimus.Methods: 25 stable kidney transplant recipients (9 male, 16 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 32 publications
1
3
0
Order By: Relevance
“…Regardless of interval glucocorticoid exposure and BMI-Z, treatment with cyclosporine versus tacrolimus was associated with higher SBP-Z and DBP-Z. These findings are consistent with other studies in renal and other solid organ transplant recipients demonstrating a greater burden of hypertension with cyclosporine compared with tacrolimus immunosuppression [49][50][51].…”
Section: Discussionsupporting
confidence: 91%
“…Regardless of interval glucocorticoid exposure and BMI-Z, treatment with cyclosporine versus tacrolimus was associated with higher SBP-Z and DBP-Z. These findings are consistent with other studies in renal and other solid organ transplant recipients demonstrating a greater burden of hypertension with cyclosporine compared with tacrolimus immunosuppression [49][50][51].…”
Section: Discussionsupporting
confidence: 91%
“…Previous studies in renal transplant recipients demonstrated that conversion from CS to TAC immunosuppression reduces the progression of chronic kidney disease (CKD) 11–13 . This may be attributed to a lower expression of profibrotic genes, such as transforming growth factor (TGF)‐beta I and fewer adverse effects on renal haemodynamics in TAC‐treated patients 14–16 .…”
Section: Introductionmentioning
confidence: 99%
“…There are also differences in the non-renal toxic effects of cyclosporine versus tacrolimus 71 which often influence the choice of CI in a particular patient. Post-transplant diabetes mellitus, neurotoxicity, cephalea, diarrhea, and hypomagnesemia were observed more commonly after tacrolimus treatment.…”
Section: Comparison Of Toxic Effects Of Both CImentioning
confidence: 99%